Continuous culture of Nitrosomonas eutropha and biomethanol production using whole cell biotransformation. Issue 5 (25th January 2021) - Sabale, Tushar; Babu, Mohan; Panchwagh, Shruti; Ghosalkar, Anand
Abstract: BACKGROUND: Nitrosomonas eutropha is a chemolithoautotrophic organism with an ability to oxidize ammonium to nitrite and nitrate. Continuous culture with and without cell recycling was used to enhance production of N. eutropha cell biomass using a 40‐L bioreactor. Whole cell biotransformation was used to convert methane (CH4 ) present in the biogas into biomethanol using N. eutropha. RESULTS: The maximum biomass production rate of N. eutropha was increased by three‐fold with provision of cell recycling in the continuous culture. Removal of nitrite from the continuous culture resulted in high activity of ammonia monooxygenase enzyme responsible for conversion of CH4 to biomethanol. Use of ammonium sulfate as a source of electrons for biotransformation reaction with N. eutropha resulted in a maximum 119.86 mg L −1 of biomethanol production. CONCLUSION: Our research provides an efficient process for biomass production of N. eutropha using continuous culture. We have demonstrated improvement in CH4 to biomethanol conversion using biogas as feedstock. © 2021 Society of Chemical Industry